Determination of methane emission rates on a biogas plant using data from laser absorption spectrometry. (February 2015) - Groth, Angela; Maurer, Claudia; Reiser, Martin; Kranert, Martin
Highlights: Remote sensing measurements provide methane concentrations of biogas plants. Inverse dispersion modeling deduces methane emission rates. Different operating conditions of the plant can roughly be represented. Higher methane emissions indicate leakages or open pressure relief valves. Open digestate storage tanks or active stirring lead to higher gas releases. Abstract: The aim of the work was to establish a method for emission control of biogas plants especially the observation of fugitive methane emissions. The used method is in a developmental stage but the topic is crucial to environmental and economic issues. A remote sensing measurement method was adopted to determine methane emission rates of a biogas plant in Rhineland-Palatinate, Germany. An inverse dispersion model was used to deduce emission rates. This technique required one concentration measurement with an open path tunable diode laser absorption spectrometer (TDLAS) downwind and upwind the source and basic wind information, like wind speed and direction. Different operating conditions of the biogas plant occurring on the measuring day (December 2013) could be represented roughly in the results. During undisturbed operational modes the methane emission rate averaged 2.8 g/s, which corresponds to 4% of the methane gas production rate of the biogas plant.